PENGARUH MOTIVASI DIRI TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA - Desrizal, Muhammad Hafiz; Wijanarko, Adrian Azhar (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of self-motivation on entrepreneurial interest in students. A quantitative descriptive methodology was used, utilizing purposive sampling with the criteria that the respondents involved in this study were students. This study involved a sample of 101 respondents. The analysis methods used are Descriptive Method and Multiple Regression Analysis with SPSS ver.26. Data collection was facilitated through the distribution of questionnaires in the form of Google Form Questionnaires distributed to respondents using a scale range of 1-5 with the criteria of strongly disagree, disagree, neutral, agree and strongly agree.  The results of the study were obtained that there was a significant influence between self-motivation and entrepreneurial interest. Furthermore, in order for the level of self-motivation of students to be interested in entrepreneurship is increasing, Paramadina University Jakarta needs to help its students to develop their hard skills and soft skills through  the career center at Paramadina University. So that students can grow their interest in entrepreneurship, especially among Generation Z